Kajian Sadd Adz-Dzarî’ah: Jual Beli Alat Kontrasepsi Online - Nur Fadlan (Journal of Islamic Business Law, 2018)
This research aims to know the freedom of contraception and selling online, and to know the views rule Usul Fiqh sadd adz-dzarî'ah of free contraceptives and selling online. The type of research used in this study is using this type of normative research using rule Usul Fiqh sadd adz-dzarî'ah. The results of this research show the perpetrators free enterprise trading contraception online. Freedom to buy and sell online, contraceptives are not limited or very free in its implementation. Both in terms of marketing, advertising, and sales. Freedom and selling contraceptives online implementation is not limited to, in the event anyone can buy and sell contraceptives has online. In the absence of provisions of married and unmarried, adult or under. According to sadd adz-dzarî'ah selling contraceptives online when it raises the forbidden things. This includes selling helped in sin and transgression that know no limitations on who has the right to buy and use contraceptives. Then, buy sell buy prohibited or unlawful